Advances in early diagnosis of Alzheimer's disease: an overview - Qiang LUO; Ya-nan LUO; Na-na FENG (Editorial Office of Chinese Journal of Public Health, 2023)
Alzheimer's disease (AD) is one of the diseases which cause disability and mortality in older adults. Early diagnosis is of great significance for delaying the development of AD and its related function decline, which can help to achieve the aim of healthy aging. This study reviewed current research about the prediction and early diagnosis of AD, which included literature review on the fields of the development and frontiers of early diagnosis technology in humoral markers, blood markers, cognitive markers detection and digital markers. The study provides the conceptual ideas to help identify the high-risk groupsand deliver interventions accurately, and provides important reference for early diagnosis of the disease in older adults.